JENIS PAKAN DAN PERILAKU MAKAN MONYET EKOR PANJANG (Macaca fascicularis) DI ZONA PEMANFAATAN PULAU SATONDA TAMAN NASIONAL MOYO SATONDA - Chatami, Lalu Radinal Ihya; Syaputra, Maiser; Hadi, Islamul (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
Satonda Island, which is located in Dompu Regency, West Nusa Tenggara Province, is a habitat for long-tailed monkeys. This research aims to determine the type of food and eating behavior of long-tailed monkeys in the utilization zone of Satonda Island. The method used in this research isFocal animal sampling with the alpha long-tailed monkey as the research object. The results of the research show that there are 8 types of food sources for long-tailed monkeys in the utilization zone of Satonda Island, Moyo Satonda National Park, consisting of figs (fig tree), sour (Tamarindus indica), offerings (Lannea coromandelica), ivory coconut (Cocoa nuts), cherries (Muntingia calabura), ketapang (Terminalia catappa), lantana (Lantana montevidensis), and hibiscus (China rose). Acid is the most consumed feed with a percentage of 22.67%. The most eaten part is fruit with a percentage of 42%. Meanwhile, the eating behavior of long-tailed monkeys that appears most often is chewing with a percentage of 30.7%, and swallowing behavior is the least common eating behavior with a percentage of 20.4% in observations of eating behavior Keywords: Types of food, long-tailed monkeys, feeding behavior, Satonda Island.